Analysis of textbook outcomes among patients undergoing resection of retroperitoneal sarcoma: A multi‐institutional analysis of the US Sarcoma Collaborative. Issue 6 (21st July 2020) - Wiseman, Jason T.; Ethun, Cecilia G.; Cloyd, Jordan M.; Shelby, Rita; Suarez‐Kelly, Lorena; Tran, Thuy; Poultsides, George; Mogal, Harveshp; Clarke, Callisia; Tseng, Jennifer; Roggin, Kevin K.; Chouliaras, Konstantinos; et al.
Abstract: Background: The novel composite metric textbook outcome (TO) has increasingly been used as a quality indicator but has not been reported among patients undergoing surgical resection for retroperitoneal sarcoma (RPS) using multi‐institutional collaborative data. Methods: All patients who underwent resection for RPS between 2000 to 2016 from eight academic institutions were included. TO was defined as a patient with R0/R1 resection that discharged to home and was without transfusion, reoperation, grade ≥2 complications, hospital‐stay >50th percentile, or 90‐day readmission or mortality. Univariate and multivariable analyses were performed. Results: Among 627 patients, 56.1% were female and the median age was 59 years. A minority of patients achieved a TO (34.9%). Factors associated with achieving a TO were tumor size <20 cm and low tumor grade, while ASA class ≥3, history of a prior cardiac event, resection of left colon/rectum, distal pancreatic resection, major venous resection and drain placement were associated with not achieving a TO (all P  < .05). Achievement of a TO was associated with improved survival (median:12.7 vs 5.9 years, P  < .01). Conclusions: Among patients undergoing resection for RPS, failure to achieve TO is common and associated with significantly worse survival. The use of TO may inform patient expectations and serve as a measure for patient‐level hospital performance.